Plant-Growth-Promoting Rhizobacteria (PGPR) and Medicinal Plants - Egamberdieva, Dilfuza; Shrivastava, Smriti; Varma, Ajit (Soil Biology, 2015)
This book describes the various applications of microorganisms in improving plant growth, health and the efficiency of phytochemical production. The chapters trace topics such as the role of PGPRs in improving salt stress and heavy metal tolerance in plants; the prevention and control of plant diseases; boosting soil fertility and agriculture productivity; the induction of secondary metabolite biosynthesis in medicinal and aromatic plants; the enhancement of phytochemical levels, and the action mechanisms, diversity and characterization of PGPRs. The reviews will be of interest for scientists in the fields of agriculture, microbiology, soil biology, plant breeding and herbal medicinal products.